2021
DOI: 10.1109/access.2021.3075972
|View full text |Cite
|
Sign up to set email alerts
|

Protection Devices in Commercial 18650 Lithium-Ion Batteries

Abstract: Lithium-ion batteries are wildly used as power sources for portable electronics because of the standardized format and economical manufacturing cost. However, commercial 18650 cells come in various designs due to the implementation of different protection devices. The current interrupt device and top vent are mandatory protection devices for all commercial 18650 Li-ion batteries. In contrast, the positive temperature coefficient thermistor, bottom vent, and protection circuit are optional protection devices th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 19 publications
(24 reference statements)
0
32
0
Order By: Relevance
“…The first results of experimental studies showed and confirmed the reliability of the structure of cylindrical 18650 LIPC due to the presence in the structure of the element of special protection against internal overheating of the element [16]. After applying current (17 A) to the LIPC, the internal temperature of the element increased to 80-104 °C.…”
Section: Experimental Studies To Determine the Critical Indicators Of...mentioning
confidence: 71%
See 1 more Smart Citation
“…The first results of experimental studies showed and confirmed the reliability of the structure of cylindrical 18650 LIPC due to the presence in the structure of the element of special protection against internal overheating of the element [16]. After applying current (17 A) to the LIPC, the internal temperature of the element increased to 80-104 °C.…”
Section: Experimental Studies To Determine the Critical Indicators Of...mentioning
confidence: 71%
“…This fact makes it impossible to disconnect the electric circuit in the event of an increase in the internal pressure of the element and leads to intensive burning of LIPCs. In particular, it was confirmed [16] that the standard protection of cylindrical LIPCs works in the range of 80-100 °C. However, it was established that the temperature indicators of the onset of an irreversible thermochem-ical reaction are somewhat different from those already known (90-130 °C) [6] and can vary between 100-150 °C, Fig.…”
Section: Mathematical Modeling Of Panasonic Ncr18650b Heating Process...mentioning
confidence: 74%
“…If the pressure still increases within the cell, the excess pressure is released in a controlled manner through vent holes in the top cover. Apart from the PTC and CID, some cells have additional protective devices such as bottom vents and external protective circuit boards …”
Section: Safety Of Counterfeit Lithium-ion Cells and Batteriesmentioning
confidence: 99%
“…Apart from the PTC and CID, some cells have additional protective devices such as bottom vents and external protective circuit boards. 18 At the battery level, safety mechanisms including the battery management system (BMS) are used to protect batteries against off-nominal conditions. Counterfeiters may lack the knowledge to design a proper BMS, or the cells in the battery may be improperly balanced.…”
Section: ■ Safety Of Counterfeit Lithium-ion Cells and Batteriesmentioning
confidence: 99%
“…Such systems are widely implemented in cylindrical cells, but several applications in prismatic cells are also reported [10]. Another useful passive safety element present inside commercial cells is commonly known as PTC (Positive Temperature Coefficient) device [11]. It is usually included into the top cap, between the positive terminal and the CID burst disk.…”
Section: Introductionmentioning
confidence: 99%